The impact of regulatory action on the co‐prescribing of renin–angiotensin system blockers in UK primary care†. Issue 7 (11th May 2017) - Allen, Craig; Donegan, Katherine
Abstract: Purpose: The aim of this study was to assess the impact of regulatory action taken in June 2014 on the co‐prescribing of renin–angiotensin system (RAS) blockers in UK primary care. Methods: RAS blocker prescriptions, issued between 01/01/2009–30/06/2015, were extracted from the Clinical Practice Research Datalink to estimate the quarterly prevalence (number of patients with at least one co‐prescription) and incidence (number of patients first receiving a RAS blocker co‐prescription) of co‐prescribing. Two different RAS blockers prescribed on the same day constituted a co‐prescription. Results: A total of 880 364 patients were prescribed a single RAS blocker during the study period. Prevalence of co‐prescribing increased from 4812 patients per million person‐years in Q1 2009 to 4865 in Q1 2010. A reduction then occurred decreasing to 2901 patients per million person‐years in Q2 2014 when the EU review concluded and continued to decrease thereafter despite a continued increase in the prevalence of prescribing of a single RAS blocker. Incidence of new co‐prescribing decreased from 454 patients per million person‐years in Q1 2009 to 159 in Q2 2014, but remained relatively constant at ~119 patients per million person‐years on average after the EU review concluded. A total of 96% of co‐prescriptions were for an ACE inhibitor + ARB, and 4% accounted for an ACE inhibitor or ARB + renin inhibitor. Conclusions: Recently, there has been a decrease in the prevalence and incidence of RAS blocker co‐prescribing. Reassuringly, overall co‐prescribing reduced in line with recommendations, although there was a decreasing trend prior to this likely due in part to prior publication of the data used in the EU review. © 2017 Crown copyright. Pharmacoepidemiology and Drug Safety © 2017 John Wiley & Sons, Ltd.